Divergent Cardiac Adaptations in Endurance Sport: Atrial Fibrillation Markers in Marathon Versus Ultramarathon Athletes - Zbigniew Waśkiewicz; Eduard Bezuglov; Oleg Talibov; Robert Gajda; Zhassyn Mukhambetov; Daulet Azerbaev; Sergei Bondarev (Journal of Cardiovascular Development and Disease, 2025)
Endurance training induces significant cardiac remodeling, with evidence suggesting that prolonged high-intensity exercise may increase the risk of atrial fibrillation (AF). However, physiological responses differ by event type. This review compares AF-related markers in marathon and ultramarathon runners, focusing on structural adaptations, inflammatory and endothelial biomarkers, and the incidence of arrhythmias. A systematic analysis of 29 studies revealed consistent left atrial (LA) enlargement in marathon runners linked to elevated AF risk and fibrosis markers such as Galectin-3 and PIIINP. In contrast, ultramarathon runners exhibited right atrial (RA) dilation and increased systemic inflammation, as indicated by elevated high-sensitivity C-reactive protein (hs-CRP) and soluble E-selectin levels. AF incidence in marathoners ranged from 0.43 per 100 person-years to 4.4%, while direct AF incidence data remain unavailable for ultramarathon populations, highlighting a critical evidence gap. These findings suggest distinct remodeling patterns and pathophysiological profiles between endurance disciplines, with implications for athlete screening and cardiovascular risk stratification.